The time course of speaker-specific language processing. (August 2021) - Kroczek, Leon O.H.; Gunter, Thomas C.
Abstract: Listeners are sensitive to a speaker's individual language use and generate expectations for particular speakers. It is unclear, however, how such expectations affect online language processing. In the present EEG study, we presented thirty-two participants with auditory sentence stimuli of two speakers. Speakers differed in their use of two particular syntactic structures, easy subject-initial SOV structures and more difficult object-initial OSV structures. One speaker, the SOV-Speaker, had a high proportion of SOV sentences (75%) and a low proportion of OSV sentences (25%), and vice-versa for the OSV-Speaker. Participants were exposed to the speakers' individual language use in a training session followed by a test session on the consecutive day. ERP-results show that early stages of sentence processing are driven by syntactic processing only and are unaffected by speaker-specific expectations. In a late stage, however, an interaction between speaker and syntax information was observed. For the SOV-Speaker condition, the classical P600-effect reflected the effort of processing difficult and unexpected sentence structures. For the OSV-Speaker condition, both structures elicited different responses on frontal electrodes, possibly indexing effort to switch from a local speaker model to a global model of language use. Overall, the study identifies distinct neural mechanisms related to speaker-specific expectations.